Cane Hay Cost-Return Budget in Western Kansas - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Holman, John; Haag, Lucas (My University, 2014)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_2014_02
Keywords: MF997; Economics; Crops; MF